Professional Commitment in Terms of Gender and Tenure of Vocational High School Teachers - Umi Anugerah Izzati; Nurchayati Nurchayati; Yuri Lolita; Olievia Prabandini Mulyana (IJORER : International Journal of Recent Educational Research, 2022)
To perform effectively, teachers must have a strong professional commitment. This quantitative and comparative study examines how gender and tenure can contribute to differences in professional commitment. Subjects who participated in this study amounted to 89 people consisting of 33 female teachers and 56 male teachers at Vocational High School in Surabaya and number of teachers who have tenure more than 10 years is 22 people, while 44 people with 1-2 tenure, 23 people with 3-10 tenure. Using SPSS 25.0 for Windows, two-way ANOVA revealed no statistically significant difference in professional commitment between male and female teachers (significance level 0.097 with p > 0.05). We also found that tenure had a statistically significant effect on professional commitment (significance level 0.013 with p < 0.05). This study shows that teachers with longer tenures exhibit greater levels of professional commitment.